Effects of grazing on soil respiration and associated factors in artificial Caragana korshinskii shrublands in Inner Mongolia, China - Wu, Hao; Deng, Xiaodong; Li, Xinghua; Gao, Shaobo; Yuan, Ruihan; Li, Jiayan; Min, Haotian; Ma, Xiuzhi (Frontiers in Environmental Science, 2025)
Investigating the impact of grazing on soil respiration in artificial Caragana korshinskii is crucial for harmonizing the carbon sequestration potential of ecological restoration with the sustainable development of animal husbandry. This research is directly linked to addressing the challenges of carbon balance regulation in arid regions and mitigating the conflict between forestry and livestock farming. Continuous grazing modifies biomass and soil properties in artificial C. korshinskii shrublands, potentially influencing soil respiration. To assess the effects of grazing on soil respiration in artificial C. korshinskii shrublands, we established three experimental plots (no grazing, light grazing, and heavy grazing) in the northern foothills of the Daqing Mountains in Inner Mongolia in 2022. Soil respiration, physicochemical properties, and biomass were monitored throughout the growing season. The study results indicate that: (1) No significant difference in soil respiration was observed in C. korshinskii shrublands under grazing conditions. (2) The chemical properties of surface soil may serve as the primary regulatory factors influencing soil respiration under grazing conditions. Based on the average level of soil respiration under different grazing intensities, to effectively mitigate soil carbon emissions, we recommend a moderate reduction in the grazing intensity of C. korshinskii shrublands in arid and semi-arid agro-pastoral regions.